1988
DOI: 10.1016/0090-8258(88)90047-9
|View full text |Cite
|
Sign up to set email alerts
|

Cervical carcinoma antigen: Distribution in neoplastic lesions of the uterine cervix and comparison to other tumor markers

Abstract: Four antibodies (anti-CCA, anti-CEA, Ca-l, and anti-EMA) were used to study the distribution of antibody-binding sites in normal endocervical mucosa, metaplastic squamous epithelium, squamous epithelium exhibiting varying grades of intraepithelial neoplasia, and invasive squamous cell carcinoma. Anti-CCA, a novel monoclonal antibody raised against an extract of squamous cell carcinoma of the cervix, recognizes dysplastic, neoplastic, and metaplastic cervical epithelial cells. While anti-CCA and Ca-l rarely sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Immunohistochemical methods have demonstrated CEA in all cases of CIN and 71% of invasive carcinomas but absence in normal squamous and glandular epithelium [1]. In contrast, Flint et al [11] found that 31% of normal glandular cervical epithelium stained with anti-CEA antibody. Parallel immunohistochemical tests for CEA antibodies in low-grade CIN showed no differences regarding regression, persistence or progression of the lesions [15].…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical methods have demonstrated CEA in all cases of CIN and 71% of invasive carcinomas but absence in normal squamous and glandular epithelium [1]. In contrast, Flint et al [11] found that 31% of normal glandular cervical epithelium stained with anti-CEA antibody. Parallel immunohistochemical tests for CEA antibodies in low-grade CIN showed no differences regarding regression, persistence or progression of the lesions [15].…”
Section: Discussionmentioning
confidence: 99%
“…Clear cell ACs have been reported by some authors to show immunoreactivity for CEA,24,25,31 CA 19-9,23 and CA 125,~-~ ~~w hile other authors23.24,25.30,36 noted negative re-sults for CEA, PLAP, CA, and vimentin. In one study, squamous carcinomas of the cervix were uniformly positive for CEA 28. …”
mentioning
confidence: 97%
“…Benign morular (squamous) metaplasia is present. 83 of the cases showed 33 positive for monoclonal carcinoembryonic antigen (CEA-M),38 positive for polyclonal CEA (CEA-P),26 positive for placental alkaline phosphatase, 18 positive for CA 125, 29 positive for CA 19-9, 24 positive for vimentin, 60 positive for CK CAM 5.2, and 81 positive for cytokeratin AE 1 :3 (CK AE1/3). Immunohistochemical staining pattern varied from predominantly lumenal to predominantly cytoplasmic(Fig.…”
mentioning
confidence: 99%